Vertical (arboreality) and horizontal (dispersal) movement increase the resilience of vertebrates to climatic instability - Brett. R. Scheffers; Luke Shoo; Ben Phillips; Stewart L. Macdonald; Alex Anderson; Jeremy VanDerWal; Collin Storlie; Arnaud Gourret; Stephen E. Williams (Global Ecology and Biogeography, 2017)
Aim Species that respond favourably to environmental change tend to be mobile or dispersive. Living within trees has some benefits over life on the ground. Species that move vertically within forest canopies can take advantage of increased complexity and resource availability, which should correspond to increased resilience to environmental variability and change. Here we show that two modes of movement, arboreality and horizontal dispersal, across an entire bioregional vertebrate fauna in the rain forests of Australia are associated with measures of historical environmental stability. Location Wet Tropics, Queensland, Australia. Time period Historical (c. 20,000 years ago) and current (1990‐2009). Major taxa studied Mammal, bird, reptile, and frog species. Methods We analysed vertebrate distribution for 195 species and trait data from 20 years of standardized sampling. We derived an arboreality index (i.e., the extent of vertical habitat used by each species) from a large database of field observations combined with expert opinion scores on arboreality. We compared community‐wide trends in arboreality and their horizontal dispersal potential with historical climate since the Last Glacial Maximum ( c . 20,000 years ago) and current climate over 20 years of the recent past (1990–2009). Results Vertical (arboreality) and horizontal (dispersal) movement were positively correlated, and both were negatively correlated with environmental stability. We found that arboreal species dominate communities in historically unstable areas, and these areas have both low richness and low endemism. Further, we show that low‐ and high‐altitude arboreal species experience similar thermal regimes, whereas low‐ and high‐altitude ground‐dwelling species experience little overlap in thermal regimes. Main conclusion Higher variability and overlap in temperature among rain forest canopies suggests less geographical separation in tolerable conditions for arboreal taxa when compared with ground‐dwelling taxa. Increased ecological plasticity in horizontal and vertical movement as well as exposure and pre‐selection to high temperature variability appears to allow arboreal species to exploit climatically uncertain areas, a capacity that may serve them well in responding to future climate change.

Slow recovery of tropical old‐field rainforest regrowth and the value and limitations of active restoration - Luke P. Shoo; Kylie Freebody; John Kanowski; Carla P. Catterall (Conservation Biology, 2016)
There is current debate about the potential for secondary regrowth to rescue tropical forests from an otherwise inevitable cascade of biodiversity loss due to land clearing and scant evidence to test how well active restoration may accelerate recovery. We used site chronosequences to compare developmental trajectories of vegetation between self‐organized (i.e., spontaneous) forest regrowth and biodiversity plantings (established for ecological restoration, with many locally native tree species at high density) in the Australian wet tropics uplands. Across 28 regrowth sites aged 1–59 years, some structural attributes reached reference rainforest levels within 40 years, whereas wood volume and most tested components of native plant species richness (classified by species’ origins, family, and ecological functions) reached less than 50% of reference rainforest values. Development of native tree and shrub richness was particularly slow among species that were wind dispersed or animal dispersed with large (>10 mm) seeds. Many species with animal‐dispersed seeds were from near‐basal evolutionary lineages that contribute to recognized World Heritage values of the study region. Faster recovery was recorded in 25 biodiversity plantings of 1–25 years in which wood volume developed more rapidly; native woody plant species richness reached values similar to reference rainforest and was better represented across all dispersal modes; and species from near‐basal plant families were better (although incompletely) represented. Plantings and regrowth showed slow recovery in species richness of vines and epiphytes and in overall resemblance to forest in species composition. Our results can inform decision making about when and where to invest in active restoration and provide strong evidence that protecting old‐growth forest is crucially important for sustaining tropical biodiversity.

Quantitative tools and simultaneous actions needed for species conservation under climate change-Reply to Shoo et al. (2013) - Luke P. Shoo; Ary A. Hoffmann; Stephen Garnett; John K. Scott; Stephen E. Williams (Climatic Change, 2015)

Moving beyond the conceptual: specificity in regional climate change adaptation actions for biodiversity in South East Queensland, Australia - Luke P. Shoo; Julian O’Mara; Karin Perhans; Jonathan R. Rhodes; Rebecca K. Runting; Susanne Schmidt; Lochran W. Traill; Lui C. Weber; Kerrie A. Wilson; Catherine E. Lovelock (Regional Environmental Change, 2014)

Patterns of rain forest plant endemism in subtropical Australia relate to stable mesic refugia and species dispersal limitations - Lui C. Weber; Jeremy VanDerWal; Susanne Schmidt; William J. F. McDonald; Luke P. Shoo (Journal of Biogeography, 2014)
Aim Our aims were to identify centres of endemism and to infer whether these areas have functioned as refugia for subtropical rain forest plants through historical climate fluctuations. Location Subtropical eastern A ustralia (23–33° S; 145–155° E). Methods We collated 25,000 records of 179 endemic rain forest plants to identify geographical areas with unusually high concentrations of endemic taxa and range‐restricted endemics. We then tested whether centres of endemism coincide with other features indicating refugia, including habitat stability over 120,000 years, and we related dispersal patterns to past habitat stability using seed weight as a surrogate for dispersal ability of endemic plant taxa. Results We identified five main centres of endemism. Historical stability and other processes affecting diversity, including current rainfall, rain forest area, and topographic complexity, explained 58% of variation in plant‐weighted endemism. Taxa with poor dispersal ability were concentrated in the areas that were most stable historically. Main conclusions Several lines of evidence suggest that centres of endemism have functioned as important refugia for subtropical rain forest taxa through historical climate fluctuations. The highest concentrations of range‐restricted endemic species occur in locations that are predicted to have maintained stable rain forest habitat over at least the past 120,000 years. This association was independent from other factors that were expected to promote diversity (i.e. rain forest area and current environmental suitability). These locations have disproportionately high concentrations of species with poor dispersal ability (large‐seeded species).

Making decisions to conserve species under climate change - Luke P. Shoo; Ary A. Hoffmann; Stephen Garnett; Robert L. Pressey; Yvette M. Williams; Martin Taylor; Lorena Falconi; Colin J. Yates; John K. Scott; Diogo Alagador; Stephen E. Williams (Climatic Change, 2013)

Immigrants and refugees: the importance of dispersal in mediating biotic attrition under climate change - Alex S. Anderson; April E. Reside; Jeremy J. VanDerWal; Luke P. Shoo; Richard G. Pearson; Stephen E. Williams (Global Change Biology, 2012)
Montane tropical rainforests are critically important areas for global bird diversity, but are projected to be highly vulnerable to contemporary climate change. Upslope shifts of lowland species may partially offset declines in upland species but also result in a process of lowland biotic attrition. This latter process is contingent on the absence of species adapted to novel warm climates, and isolation from pools of potential colonizers. In the A ustralian Wet Tropics, species distribution modelling has forecast critical declines in suitable environmental area for upland endemic birds, raising the question of the future role of both natural and assisted dispersal in species survival, but information is lacking for important neighbouring rainforest regions. Here we use expanded geographic coverage of data to model the realized distributions of 120 bird species found in north‐eastern A ustralian rainforest, including species from potential source locations in the north and recipient locations in the south. We reaffirm previous conclusions as to the high vulnerability of this fauna to global warming, and extend the list of species whose suitable environmental area is projected to decrease. However, we find that expansion of suitable area for some species currently restricted to northern rainforests has the potential to offset biotic attrition in lowland forest of the A ustralian Wet Tropics. By examining contrasting dispersal scenarios, we show that responses to climate change in this region may critically depend on dispersal limitation, as climate change shifts the suitable environmental envelopes of many species south into currently unsuitable habitats. For lowland and northern species, future change in vegetation connectivity across contemporary habitat barriers is likely to be an important mediator of climate change impacts. In contrast, upland species are projected to become increasingly isolated and restricted. Their survival is likely to be more dependent on the viability of assisted migration, and the emergence and persistence of suitable environments at recipient locations.

Potential for mountaintop boulder fields to buffer species against extreme heat stress under climate change - Luke P. Shoo; Collin Storlie; Yvette M. Williams; Stephen E. Williams (International Journal of Biometeorology, 2010)

Global potential net primary production predicted from vegetation class, precipitation, and temperature: comment - Luke P. Shoo; Vanessa Valdez Ramirez (Ecology, 2010)

New approaches to understanding late Quaternary climate fluctuations and refugial dynamics in Australian wet tropical rain forests - Jeremy VanDerWal; Luke P. Shoo; Stephen E. Williams (Journal of Biogeography, 2009)
Aim We created spatially explicit models of palaeovegetation stability for the rain forests of the Australia Wet Tropics. We accounted for the climatic fluctuations of the late Quaternary, improving upon previous palaeovegetation modelling for the region in terms of data, approach and coverage of predictions. Location Australian Wet Tropics. Methods We generated climate‐based distribution models for broad rain forest vegetation types using contemporary and reconstructed ‘pre‐clearing’ vegetation data. Models were projected onto previously published palaeoclimate scenarios dating to c. 18 kyr bp . Vegetation stability was estimated as the average likelihood that a location was suitable for rain forest through all climate scenarios. Uncertainty associated with model projections onto novel environmental conditions was also tracked. Results Upland rain forest was found to be the most stable of the wet forest vegetation types examined. We provide evidence that the lowland rain forests were largely extirpated from the region during the last glacial maximum, with only small, marginally suitable fragments persisting in two areas. Models generated using contemporary vegetation data underestimated the area of environmental space suitable for rain forest in historical time periods. Model uncertainty resulting from projection onto novel environmental conditions was low, but generally increased with the number of years before present being modelled. Main conclusions Climate fluctuations of the late Quaternary probably resulted in dramatic change in the extent of rain forest in the region. Pockets of high‐stability upland rain forest were identified, but extreme bottlenecks of area were predicted for lowland rain forest. These factors are expected to have had a dramatic impact on the historical dynamics of population connectivity and patterns of extinction and recolonization of dependent fauna. Finally, we found that models trained on contemporary vegetation data can be problematic for reconstructing vegetation patterns under novel environmental conditions. Climatic tolerances and the historical extent of vegetation may be underestimated when artificial vegetation boundaries imposed by land clearing are not taken into account.

Potential decoupling of trends in distribution area and population size of species with climate change - Luke P. Shoo; Stephen E. Williams; Jean‐Marc Hero (Global Change Biology, 2005)
Global climates are changing rapidly and biological responses are becoming increasingly apparent. Here, we use empirical abundance patterns across an altitudinal gradient and predicted altitudinal range shifts to estimate change in total population size relative to distribution area in response to climate warming. Adopting this approach we predict that, for nine out of 12 species of regionally endemic birds, total population size will decline more rapidly than distribution area with increasing temperature. Two species showed comparable loss and one species exhibited a slower decline in population size with change in distribution area. Population size change relative to distribution area was greatest for those species that occurred at highest density in the middle of the gradient. The disproportional loss in population size reported here suggests that extinction risk associated with climate change can be more severe than that expected from decline in distribution area alone. Therefore, if we are to make accurate predictions of the impacts of climate change on the conservation status of individual species, it is crucial that we consider the spatial patterns of abundance within the distribution and not just the overall range of the species.